Transjugular Intrahepatic Portosystemic Shunt for the Management of Medically Refractory Chylous Ascites in Cirrhosis: A Single-Institution Retrospective Analysis - Sasidharan, Rajesh; Suryavanshi, Shubham; Baby, Akhil; Philips, Cyriac Abby; Oommen, Tharun Tom (Journal of Clinical Interventional Radiology ISVIR, 2025)
We report our experience with using transjugular intrahepatic portosystemic shunt (TIPS) for the management of chylous ascites in cirrhotic patients. A total of eight patients were included in the final analysis. The primary outcome assessed was the resolution of ascites. Secondary outcomes, including hepatic encephalopathy (HE), sepsis, worsening of liver function, and transplant-free survival, were also evaluated. Three-month follow-up imaging showed resolution of ascites in all patients, except for one who had concurrent renal dysfunction. Two patients died 3 and 5 months after TIPS due to sepsis and multi-organ failure. The incidence of HE during the follow-up period was 25%. No patient experienced significant worsening of liver function in the early post-procedure phase. One patient received a transplant 9 months after TIPS. Mean transplant-free survival for the remaining patients was 19 months. In conclusion, TIPS is an effective treatment for managing chylous ascites in cirrhosis that is refractory to medical therapy.
Keywords: chylous; lymphatic; paracentesis